2020
DOI: 10.1080/23311843.2020.1778987
|View full text |Cite
|
Sign up to set email alerts
|

User’s opinion in scientific forest management implementation in Nepal – a case study from Nawalparasi district

Abstract: While much emphasis has been placed on scientific and policy issues in forest management, there is a lack of clarity on users' perspectives concerning the implementation of scientific forest management. To clarify this nuance, this study explores users' opinion on scientific forest management implementation, focusing on four criteria-ecological, social, economic, and technical. Twelve key informant interviews and six focus group discussions were conducted in three selected communities within Nawalparasi Distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…This, on the one hand, limited the forest product supply to the local people, and, on the other hand, led to poor forest management. Thus, SciFM implementation was viewed as an approach to enable the forestry sector of Nepal to self-sustain its timber demands [27]. In line with this, our result contributes to this discussion and provides a clear picture of the current implementation of SciFM, concerning the pattern of timber distribution in the lowland region of Nepal.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This, on the one hand, limited the forest product supply to the local people, and, on the other hand, led to poor forest management. Thus, SciFM implementation was viewed as an approach to enable the forestry sector of Nepal to self-sustain its timber demands [27]. In line with this, our result contributes to this discussion and provides a clear picture of the current implementation of SciFM, concerning the pattern of timber distribution in the lowland region of Nepal.…”
Section: Discussionsupporting
confidence: 74%
“…Overall, we found that SciFM intervention in community forest has some positive implications, although several limitations have been demonstrated by recent studies; it is accused of having decreased user power and user participation and posing threats of recentralization [31,39,65]. SciFM has focused on timber harvesting and employed technical aspects that could be a burden to forest users [27,38]. Additionally and most importantly, it could create opportunities for the local elite while neglecting the concerns of the poor [26].…”
Section: Timber Harvesting and Distribution: How The Elite Dominate Wmentioning
confidence: 77%
“…SciFM was primarily driven by social and economic interests rather than ecological concerns (Bhusal et al 2020). The policy prescriptions were designed based on limited field experiences mostly through the consultative and participatory processes with active engagement of the development partners.…”
Section: Discussionmentioning
confidence: 99%
“…However, such a recommendation never came under implementation. The workshop recommendation contradicts the existing SciFM practices, where the management prescription were similar irrespective of forest type, conditions and management objectives (see Basnyat et al 2018) The technical soundness of the SciFM remained highly contested since it focused on single commodity management, i.e., timber, promoted without demonstrating effectiveness, including the same replication of the same management approaches irrespective of forest type, condition, and species composition and (see Basnyat et al 2018;Basnyat et al 2020;Poudyal et al 2020) Moreover, governance issues, especially over-harvesting of timber, collusion with the timber trader in the selling of the timber and corruption were quite prominent (see Joshi et al 2018;Basnyat et al 2020;Bhusal et al 2020). In addition, overharvesting from the forests received major attention in the national media.…”
Section: Scientific Forest Management (Scifm) In Nepalmentioning
confidence: 99%
“…The government also successfully demonstrated that high-intensity silvicultural harvests could establish natural Sal regeneration across the Terai lowlands [112,121,122], in spite of bureaucratic hesitancy to cut live trees and uninformed reporters and conservationists mischaracterizing the shelterwood regeneration method as deforestation [123]. Users of some Sal forests even welcomed and appreciated ScFM's timber-centric agenda, since the large annual timber output of the shelterwoods [107,124,125] generated more income and employment opportunities compared to previous harvesting regimes [121,122,124,126].…”
Section: Receptionmentioning
confidence: 99%